2018
DOI: 10.1016/j.rmcr.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic arthritis due to nivolumab administration a case report and review of the literature

Abstract: Nowadays we have novel equipment for lung cancer diagnosis, however; due to lack of symptoms, lung cancer is still diagnosed at a late stage. Currently we have the following therapies for non-small cell lung cancer: a) non-specific cytotoxic agents, b) targeted therapies and c) immunotherapy. Each therapy has its own advantages and adverse effects. In the current case we will present a rare case of psoriacic arthritis that was presented after two cycles of nivolumab administration and we will also present a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
0
13
2
1
Order By: Relevance
“…Sapalidis et al presented a case report of a patient with lung adenocarcinoma in second-line treatment with nivolumab who underwent psoriatic arthritis. The patient was treated with Apremilast, interrupting immunotherapy ( 20 ). Moreover, Apalla et al reported one case of a woman with lung adenocarcinoma and nivolumab-induced psoriasis treated effectively with Apremilast.…”
Section: Discussionmentioning
confidence: 99%
“…Sapalidis et al presented a case report of a patient with lung adenocarcinoma in second-line treatment with nivolumab who underwent psoriatic arthritis. The patient was treated with Apremilast, interrupting immunotherapy ( 20 ). Moreover, Apalla et al reported one case of a woman with lung adenocarcinoma and nivolumab-induced psoriasis treated effectively with Apremilast.…”
Section: Discussionmentioning
confidence: 99%
“…In any case it is a very efficient treatment modality. However; immunotherapy in lung cancer has numerous side effects such as tumor necrosis syndrome, vitiligo, psoriasis, acute thyroiditis and hepatitis resuscitation [ [20] , [21] , [22] , [23] ]. Uveitis, pancreatitis, central nervous system disease, and peripheral neuropathies have also been reported [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover; after we acquire biopsy we investigate for the following gene expressions growth factor receptor (EGFR) or T790M, anaplastic lymphoma kinase (ALK), Programmed death-ligand 1 (PD-L1), Proto-oncogene tyrosine-protein kinase ROS-1, R ET proto-oncogene encodes and proto-oncogene B-Raf (9,12). All these treatments of course have their adverse effects that the treating physician has to overcome (13,14).…”
Section: Introductionmentioning
confidence: 99%